2016
DOI: 10.1590/0103-6440201600693
|View full text |Cite
|
Sign up to set email alerts
|

Strontium Ranelate Effect on the Repair of Bone Defects and Molecular Components of the Cortical Bone of Rats

Abstract: This study was conducted to evaluate the effects of treatment with strontium ranelate (SR) on the repair of bone defects and molecular components of bones in femurs. Adult female rats (n=27) were subjected to ovariectomy (OVX) or Sham surgery. Thirty days after surgery, a defect was made in the femur and the animals were then divided into three groups: OVX, SHAM and OVX+SR. Euthanasia was performed four weeks after the bone defect surgery. Repair in bone defect was assessed by computed microtomography (μCT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Therefore, the effects of strontium ranelate on alveolar bone metab- and number, some investigations failed to observe any effect of this medication on osteoblast numbers and indicated that strontium ranelate inhibits mineralization and decreases collagen cross-linking in bone. 38,39 Based on the current immunohistochemical findings, it is hypothesized that most of the histometric benefits induced by strontium ranelate on ligature-induced bone resorption rely on its anti-resorptive rather than its anabolic action. Therefore, the dual effects of strontium ranelate might be not verified under an infectiousinflammatory state and this medication may present differences in the mode of its action according to different environmental factors influencing bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of strontium ranelate on alveolar bone metab- and number, some investigations failed to observe any effect of this medication on osteoblast numbers and indicated that strontium ranelate inhibits mineralization and decreases collagen cross-linking in bone. 38,39 Based on the current immunohistochemical findings, it is hypothesized that most of the histometric benefits induced by strontium ranelate on ligature-induced bone resorption rely on its anti-resorptive rather than its anabolic action. Therefore, the dual effects of strontium ranelate might be not verified under an infectiousinflammatory state and this medication may present differences in the mode of its action according to different environmental factors influencing bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…These were reported in patients given a 2,000 mg daily systemic dose treatment of SrRn for a year 50 . However, it is reasonable to suppose that topical application during vital pulp therapy may pose a much lower risk of side effects compared to systemic application 32 , 37 , 51 , 52 ; in vivo studies using rat models reported that systemic use of SrRn (625 g/kg) is well tolerated and safe with no adverse side effects 53 , 54 . However, it is necessary to evaluate the systemic side effects induced by the local application of SrRn before its clinical application.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the safety of SR, in vivo studies using rat models reported that the systemic use of SR (up to 625 g/kg daily) is well tolerated and safe, with no adverse effects . In a recent review of studies on the clinical use of SR for the management of osteoporosis (2 g/day), Reginster et al (2015) concluded that SR has an excellent benefit‐risk ratio, provided that its contraindications, including uncontrolled hypertension and a history of ischemic episodes, are respected.…”
Section: Discussionmentioning
confidence: 99%